Impact of Social Determinants of Health on Chronic Kidney Disease: A Review of Disparities in Renal Transplantation: Socioeconomic Impact on Kidney Transplant - Lombardi, Conner; Glosser, Logan; Knauss, Hanna; Norwood, Teanya; Berry, Julia; Ekwenna, Obinna (Translation: The University of Toledo Journal of Medical Sciences, 2021)
Background: Striking disparity exists in the incidence and treatment of chronic kidney disease (CKD) secondary to individual social determinants of health. Additionally, the uninsured, minority racial-ethnic groups, and Medicaid enrollees receive less nephrology care prior to being diagnosed with end-stage renal disease (ESRD). The most effective treatment for the management of kidney failure is kidney transplantation. This review addresses how social determinants of health impact the workup for patients with ESRD, with emphasis on the kidney transplant process. Methods: A search was conducted via multiple online databases (MedLine, PubMed, etc.) for articles that addressed the interplay between CKD, ESRD and kidney transplantation with the social determinants of health. Findings: The impact of the social determinants of health on CKD, ESRD, and the kidney transplantation process can be qualitatively and quantitatively measured using the five categories of education, health care and access, economic stability, neighborhood and built environment, and social and community context. Conclusion: Social determinants of health impact outcomes in CKD, ESRD, and kidney transplantation. Public and private initiatives aimed at reducing social disparities among patients with kidney disease must include emphasis on education, health care and access, economic stability, neighborhood and built environment, and social and community context. This initiative is necessary to prevent progression to ESRD and to ensure quality care in the kidney transplantation process.